A Study On the Effects of Video Games On Behavioral Change - Kalaiselvan, S; Branesh, A.K; Senthil Kumar, B; Kalimuthu, A (International Journal of Computer Sciences and Engineering, 2018)
This research paper aimed to study the effect of video games and violence behaviour of the college students. Also, this research tries to study the relationship between the exposure level and the aggressiveness level. Prolonged exposure to video games, even the mundane ones, leads to repetitive stress injuries or addiction. Playing video games with violent content are linked to more aggressive behavior in teens. In interactive video games, players are encouraged to identify with and role plays their favorite characters. In a video game about stockcars, winning may mean winning the race. Many of the popular games played by the youngsters have fighting sequence. Violent video games do increase aggression, but other factors contribute to real life violent behavior and it is the parent’s responsibility to imprint good morals onto the child. Violent video games are significantly associated with: increased aggressive behaviour, thoughts, and affect; increased physiological arousal; and decreased prosaically (helping) behaviour. But it helps to flush out one’s anger, stress and depression. Aggressive behaviors occur in natural environments does not make them "normal" play behavior, but it does increase the face validity of the measures. Younger children are more negatively affected than young adults and males are more affected than females. The practiced youngsters can handle the stress better than others who don’t play. Also, they can actually feel less depressed and stressful. Non frequent players are consistently affected by brief exposures. The development of the increased aggressive behaviour is linked to the amount of time youngsters are allowed to use video games. There are plenty of research opportunity is available in the field of game addiction and behavioural change.